2007
DOI: 10.5194/cp-3-513-2007
|View full text |Cite
|
Sign up to set email alerts
|

Surface thermal perturbations of the recent past at low latitudes – inferences based on borehole temperature data from Eastern Brazil

Abstract: Abstract. Borehole temperature data from the eastern parts of Brazil has been examined in an attempt to extract information on surface thermal perturbations of the recent past at low latitudes. Forward models were employed in the analysis of temperature logs from 17 localities and, in addition, Bayesian inverse modeling was carried out for data from 14 selected sites. The model results have allowed determination of the magnitude as well as the duration of ground surface temperature (GST) changes in three major… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…For instance, some studies have used boreholes as shallow as 100-150 m (e.g. Majorowicz et al, 1999;Majorowicz and Safanda, 2001;Majorowicz et al, 2002;Hamza et al, 2007), while the many global analyses typically set the minimum depth criterion at 200 m thus employing boreholes 200 m or deeper Harris and Chapman, 2001;Beltrami, 2002;Beltrami and Bourlon, 2004;Pollack and Smerdon, 2004). Our calculations suggest that these depths are likely too shallow, but several caveats are necessary and discussed below.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For instance, some studies have used boreholes as shallow as 100-150 m (e.g. Majorowicz et al, 1999;Majorowicz and Safanda, 2001;Majorowicz et al, 2002;Hamza et al, 2007), while the many global analyses typically set the minimum depth criterion at 200 m thus employing boreholes 200 m or deeper Harris and Chapman, 2001;Beltrami, 2002;Beltrami and Bourlon, 2004;Pollack and Smerdon, 2004). Our calculations suggest that these depths are likely too shallow, but several caveats are necessary and discussed below.…”
Section: Discussionmentioning
confidence: 83%
“…These biases consequently impact the estimated magnitude and temporal characteristics of recovered GST histories. Large-scale analyses that involve comparisons of results from deep and very shallow borehole temperature logs (<200 m) (Majorowicz et al, 1999;Majorowicz and Safanda, 2001;Majorowicz et al, 2002;Hamza et al, 2007), yield results that are difficult to evaluate because of potential biases due to preferential depth ranges within regions. This potential bias does not disappear using simultaneous inversion since, as shown in Beltrami et al (1997), the resulting GST histories are dominated by the deepest temperature log or those with larger sampling rates.…”
Section: Discussionmentioning
confidence: 99%
“…4. History of ground surface temperature variations associated with climate changes of the recent past, deduced on the basis of functional space inversion models fits to borehole temperature profiles, for selected localities in South America (Adapted with modifications from Hamza et al, 2007).…”
Section: Results Of Functional Space Inversionmentioning
confidence: 99%
“…Data acquired at shallow depths of less than 20 meters were excluded from analyses for climate changes, avoiding thereby eventual perturbing effects of diurnal and seasonal variations in the reconstruction of surface temperature history. In an earlier study Hamza et al (2007) reported results of geothermal measurements for a number of sites in the Brazilian territory. In the present we have included results of additional studies carried out during the period of 2006 to 2011.…”
Section: Selection Criteria For Climate Studiesmentioning
confidence: 99%
“…The corresponding root-mean squared error (RMSE) of each estimated linear model is always < 0.01 • C (R-square adjusted > 99.9 %), which means that the errors in the estimation of the geothermal gradients have only minor impacts on the subsequent temperature-depth anomalies. The low borehole depths require a word of caution, as some authors have indicated that a depth of 200 m may be too shallow for climate change assessments (Beltrami et al, 2011;Hamza et al, 2007;Majorowicz et al, 1999). Indeed, the Global Database of Borehole Temperatures and Climate Reconstruc- Since no other geothermal-paleoclimatological observatory is available in Portugal, the conclusions derived from these borehole profiles may be provisional.…”
Section: Consistency With Borehole Measurements and Paleoclimate Simumentioning
confidence: 99%